Physical confinement alters cytoskeletal contributions towards human mesenchymal stem cell migration. Issue 3 (19th January 2018) - Doolin, Mary T.; Stroka, Kimberly M.
Abstract: The in vivo microenvironment is critical for providing physico‐chemical signaling cues which ultimately regulate human mesenchymal stem cell (hMSC) behavior in clinically‐relevant applications. hMSCs experience mechanical confinement of the cell body and nucleus in three dimensional (3D) tissues during homing and in porous tissue engineered scaffolds, yet the effects of this mechanical cue on hMSC migration are not known. Here, we use a microchannel device to systematically examine the effect of confinement on hMSC migration and cytoskeletal organization. Notably, we show that hMSC actin and microtubules change from filamentous in unconfined spaces to a more diffuse network in confinement, and that confinement abrogates the presence of paxillin‐rich focal adhesions seen in 2D. Furthermore, several morphological parameters of the hMSC body are altered in confinement. Interestingly, hMSC speed displays a biphasic trend as a function of confinement, and increasing hMSC passage number decreases speed in all but the narrowest microchannels. Confinement also alters the relative contributions of cytoskeletal (i.e., actin and microtubule) and contractile (i.e., myosin II and Rho kinase) machinery in hMSC migration in unconfined and confined spaces. These results provide an improved understanding of how hMSCs navigate mechanical confinement, which is a central component of complicated 3D microenvironments. Hence, this work may provide insight towards more effective control of hMSC localization in porous tissue engineered scaffolds and mobilization to distinct tissue sites during homing after clinical therapy.